UPAYA PENINGKATAN SDM DAN DAYA SAING IKM MELALUI PELATIHAN MANAJEMEN MUTU DAN PENGELOLAAN SENTRA IKM: Efforts To Improve Human Resources And Competitiveness Of Small And Medium Enterprise Through Quality Management Training And Management Of SME Centers - Bakhtiar Abbas; Abdul Razak; Mahmudin A. Sabilalo; Nofal Supriaddin; Muh Nur; Asraf Asraf; Abdul Hakim; Rince Tambunan; Indira Yuana (Pakis Journal Institute, 2023)
The training was conducted with the aim of increasing the capacity of knowledge, understanding, and analytical skills for members of small and medium industries, especially about efforts to increase human resources and industrial competitiveness. Method of implementation of Community Service (PKM) activities in the form of technical guidance. The speakers in this training are academics from the PKM STIE Enam Enam Kendari Team, and at the end of the activity will be given a handbook material. Community service activities at Small and Medium EnterpriseÂ (SME) Kendari City have been carried out with positive results on the development program and the implementation of quality management and management of SME centers. In the implementation of these activities, the following conclusions can be drawn: 1). The low knowledge of SME about the importance of quality management; 2). The establishment of independent SME groups from various businesses both on the scale of small, medium and large enterprises will make it easier to obtain credit assistance and management coaching systems to increase production volumes; 3). Consultation and quality management coaching in Small and Medium Industries; 4). Application of quality management.